Porous weblike network of InSe on a compact layer by electrodeposition - Gujar, T. P.; Kim, Woo-Young; Jung, Kwang-Deog; Joo, Oh-Shim (ELECTROCHEMICAL SOC INC, 2008)
A porous, weblike network with a compact layer of InSe was fabricated on tin-doped indium oxide (ITO) coated glass substrate by the electrodeposition method from an aqueous acidic bath at room temperature. The crystal structure and stoichiometry were studied by X-ray diffraction (XRD) and energy-dispersive analysis by X-ray (EDAX) spectrums, respectively. The nucleation and growth mechanism was studied from cross-sectional and surface-view scanning electron microscopy images. XRD studies of electrodeposited InSe films reveal monoclinic and rhombohedral structures, and the EDAX spectrum confirmed the stoichiometry in the ratio of In:Se=48:52. Surface observations of produced films show a weblike network structure covering the compact layer of InSe. A compact layer is indeed initially formed onto the ITO, and seeds start to grow by a nucleation and growth mechanism. The elemental surface analysis of the core-shell nanoparticles determined by X-ray photoelectron spectroscopy confirmed the chemical nature of the material. (c) 2008 The Electrochemical Society.
Keywords: SELENIDE THIN-FILMS; CHEMICAL-VAPOR-DEPOSITION; ELECTROCHEMICAL SYNTHESIS; SOLAR-CELLS; INDIUM; GROWTH; NANOPARTICLES; SPECTROSCOPY; SUBSTRATE